Роль этического образования в формировании нравственных семейных ценностей у студентов технического образования - Жеңіснұр Күлай (World Scientific Reports, 2024)
This research paper is devoted to the role of education in the formation of moral family values among students in the context of technical and vocational education. The paper provides a theoretical overview of the main aspects of the formation of moral values, as well as the features of technical and vocational education that affect this process. The main focus is on the analysis of the role of ethical education, its methods and practices in the formation of moral beliefs and professional ethics among students. The conclusions of the work emphasize the importance of integrating ethical education into the educational process and creating a supportive educational environment for the development of moral qualities of students.